1987
DOI: 10.1063/1.338366
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved spectroscopy of Zn- and Cd-doped GaN

Abstract: Photoluminescence transients and time-resolved luminescence spectra are reported for the violet-blue emissions from epitaxial layers of Zn- and Cd-doped GaN. A typical decay time of 300 ns is reported for the blue GaN:Zn emission, peaking at about 2.89 eV. For GaN:Cd a somewhat longer decay time of τ≊1 μs dominates for the broad peak centered at ≊2.72 eV. In both cases it is concluded that the simple process involving a free-to-bound transition of an electron to a hole bound at the ZnGa, respectively, the CdGa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 20 publications
2
28
0
Order By: Relevance
“…Bergman et al used photoluminescence (PL) to derive an ionization energy of 0.34 eV for Zn. 51 Doping with Zn has not resulted in p-type conductivity, presumably due to the large ionization energy of the Zn acceptor. Experimental results about Be are inconclusive: Brandt et al have reported high levels of p-type doping using Be in MBE, provided oxygen is present as a co-dopant.…”
Section: Alternative Acceptorsmentioning
confidence: 99%
“…Bergman et al used photoluminescence (PL) to derive an ionization energy of 0.34 eV for Zn. 51 Doping with Zn has not resulted in p-type conductivity, presumably due to the large ionization energy of the Zn acceptor. Experimental results about Be are inconclusive: Brandt et al have reported high levels of p-type doping using Be in MBE, provided oxygen is present as a co-dopant.…”
Section: Alternative Acceptorsmentioning
confidence: 99%
“…Optically measured Zn level in GaN is also indicated in this figure. 27 To determine the binding energy of the Zn acceptor-bound exciton in AlN, we have measured the temperature dependence of the I 1 emission intensity in Zn doped AlN. The spectral peak position is red-shifted with increasing temperature following the variation of the bandgap.…”
Section: Zn-doped Alnmentioning
confidence: 99%
“…Zn-doped epitaxial GaN films are reported to have a dominant blue-violet emission band centered at $ 2.89 eV [4]. Hiramatsu et al have grown undoped and Zn-doped GaN films on sapphire substrates by metal organic vapor phase epitaxy (MOVPE) and reported that the Zn-doped GaN films exhibit three cathodoluminescence (CL) bands at $365, $425, and 4485 nm, corresponding to the emissions due to near band edge, violet, and blue to green, respectively [5].…”
Section: Introductionmentioning
confidence: 99%